1994
DOI: 10.1021/bi00194a009
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of the Human Granulocyte Colony-Stimulating Factor Determined by NMR Spectroscopy. Loop Mobility in a Four-Helix-Bundle Protein

Abstract: Recombinant 15N- and 13C-labeled human granulocyte colony-stimulating factor (rh-metG-CSF) has been studied by 2D and 3D NMR using uniformly labeled protein, as well as residue-specific 15N-labeled samples. Assignment of 90% of the backbone resonances and 85% of side-chain resonances has enabled the determination of both the secondary and tertiary structures of the protein. The fold is similar to those of the human growth hormone and other growth factors. Four stretches of helices were identified between resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 77 publications
8
90
2
Order By: Relevance
“…However, it is only slightly larger than the value reported for human granulocyte colony-stimulating factor ( M W = 18.9 kDa, 7, = 12.1 ns) (Zink et al, 1994), which is also composed of a four-helix bundle. In this regard, it is important to note that the rotational correlation time is dependent on the radius of the protein rather than on the molecular weight.…”
Section: Discussioncontrasting
confidence: 55%
“…However, it is only slightly larger than the value reported for human granulocyte colony-stimulating factor ( M W = 18.9 kDa, 7, = 12.1 ns) (Zink et al, 1994), which is also composed of a four-helix bundle. In this regard, it is important to note that the rotational correlation time is dependent on the radius of the protein rather than on the molecular weight.…”
Section: Discussioncontrasting
confidence: 55%
“…McKay, 1992 Feng et al, 1996Redfield et al, 1994Powers et al, 1992, 1993Muller et al, 1994Walter et al, 1992aWlodawer et al, 1992Muller et al, 1995Walter et al, 1992bRozwarski et al, 1996Milburn et al, 1993Pandit et al, 1992Hill et al, 1993Zink et al, 1994Lovejoy et al, 1993Lovejoy et al, 1993Lovejoy et al, 1993Robinson et al, 1994de Vos et al, 1992Ultsch et al, 1994Somers et al, 1994Sundstrom et al, 1996Sundstrom et al, 1996 Chantalat et aLc Abdel-Meguid et al, 1987McDonald et al, 1995Walter & Nagahhushan, 1995Zdanov et al, 1996Radhakrishnan et al, 1996Senda et al, 1995Ealick et al, 1991Samudzi et al, 1991Samudzi & Rubin, 1993Livnah et al, 1996de Vos et al, 1992Sundstrom et al, 1996Sundstrom et al, 1996Somers et al, 1994Harlos et al, 1994Muller et al, 1996Banner et al. 1996 "Cytokine or receptor class is shown along with the method of structure determination and resolution where appropriate.…”
Section: Il-6 and Helical Cytokine Structurementioning
confidence: 99%
“…Quantitative NOE measurements were possible for 147 residues, with an average value of 0.83. The heteronuclear 15 N NOE data of pl9 indicated that most of the protein backbone existed in a structure of limited conformational flexibility on a picosecond time scale, with any motions faster than the rate of overall tumbling (in nanoseconds) of small magnitude [46][47][48]. The The amino acid sequence of pl9 is divided into the five ankyrin repeats which were aligned with each other to match sequence and structurally equivalent residues.…”
Section: Conformational Stability Of Pl9mentioning
confidence: 99%
“…In addition, residues Ala-164 and Leu-166, flanking Pro-165, showed the presence of minor and major conformations in ratio 1:4.5, respectively, slowly exchanging with each other. There were also a few residues in pl9 that displayed 15 N NOE values characteristic of increased flexibility ( 15 N NOEs more than 25% smaller than the average value which has an error of ± 7%) [46][47][48]. These residues were 68, 69 and 129.…”
Section: Conformational Stability Of Pl9mentioning
confidence: 99%